Fasting blood glucose-to-glycated hemoglobin ratio and functional outcomes in patients with ischemic stroke following endovascular treatment—a meta-analysis - Hong, Chen; Wang, Xin; Chen, Hui; Sun, Ying (Frontiers in Neurology, 2025)
BackgroundStress hyperglycemia is common in acute ischemic stroke (IS) and has been linked to adverse outcomes. The fasting glucose-to-glycated hemoglobin (HbA1c) ratio (GAR) has been proposed as a simple marker reflecting stress hyperglycemia relative to chronic glycemic status. Still, its prognostic value in patients undergoing endovascular treatment (EVT) remains unclear. This meta-analysis aimed to evaluate the association between GAR and 90d-day functional outcomes in these patients.MethodsPubMed, Embase, Web of Science, Wanfang, and Chinese National Knowledge Infrastructure (CNKI) were systematically searched through May 29, 2025. Studies reporting the association between GAR and poor functional outcome, defined as a modified Rankin Scale (mRS) score of 3–6 at 90 days, were included. Odds ratios (ORs) with 95% confidence intervals (CIs) were pooled using a random-effects model accounting for heterogeneity.ResultsTwelve datasets from 10 retrospective cohort studies involving 3,878 patients were analyzed. The pooled analysis showed that a high GAR was significantly associated with an increased risk of poor functional outcome at 90 days after EVT (OR: 2.94, 95% CI: 2.22–3.88, p < 0.001; I2 = 14%). Meta-regression indicated that the proportion of diabetic patients showed a trend toward explaining the observed heterogeneity (coefficient = −0.0088, p = 0.08; I2 residual = 0%), whereas other factors showed no significant influence. Subgroup analyses yielded consistent results across age, sex, diabetes status, National Institutes of Health Stroke Scale (NIHSS), GAR cutoffs, and study quality (p for subgroup difference all > 0.05). The certainty of evidence for the primary outcome was rated as moderate according to the GRADE framework, mainly due to the retrospective design.ConclusionHigh GAR may independently predict poor 90-day functional outcomes after EVT in patients with IS, supporting its potential prognostic value in clinical practice.